Harnessing the Periplasm of Bacterial Cells To Develop Biocatalysts for the Biosynthesis of Highly Pure Chemicals - Yang, Yun (2018)
Although biocatalytic transformation has shown great promise in chemical synthesis, there remain significant challenges in controlling high selectivity without the formation of undesirable by-products. For instance, few attempts to construct biocatalysts for de novo synthesis of pure flavin mononucleotide (FMN) have been successful, due to riboflavin (RF) accumulating in the cytoplasm and being secreted with FMN. To address this problem, we show here a novel biosynthesis strategy, compartmentalizing the final FMN biosynthesis step in the periplasm of an engineered Escherichia coli strain. This construct is able to overproduce FMN with high specificity (92.4% of total excreted flavins). Such a biosynthesis approach allows isolation of the final biosynthesis step from the cytoplasm to eliminate undesirable by-products, providing a new route to develop biocatalysts for the synthesis of high-purity chemicals.